Notes for a sociology of economies based on self-management, solidarity and work in Latin America - Nicolás Goméz \~Nu\~nez (economic sociology_the european electronic newsletter, 2019)
The construction of economies invites us to reflect on the way people experience being owners and workers of their organizations, and how these communities make decisions and implement modes of production and distribution to satisfy their needs. Economic sociology deals with these matters. This approach incorporates the strength of evidence, thanks to which it avoids the biases that other inquiries have already anticipated. In the practical field of economics, however, the narrative of orthodox economic discipline produces a rhetoric whose performative capacity becomes a production force (Latour and Lépinay 2009). In the exercise of demarcations, economic sociology has included the diversity of empirical referents, conceptual repertories, and epistemic-methodological scaffolding to prevent scientific experience from being tied exclusively to the study of a market that has the capacity to transform values into prices...
Keywords: 330